- #1
Jonas E
- 15
- 0
Homework Statement
y'' + 3y' + 2y = r(t),
r(t) = u(t - 1) - u(t - 2),
y(0) = y'(0) = 0.
I need to solve this by convolution, which I know is commutative. The problem is that my calculation gives (f * g) =/= (g * f). Could someone please tell me where my mistake is?
Homework Equations
(f * g) = ∫f(τ)g(t-τ)dτ, from 0 to t
The Attempt at a Solution
I split the problem into 3 cases:
First (0 < t < 1): r(t) = 0, so y(t) = 0
Second (1 < t < 2): r(t) = 1 This is where it goes wrong.
I get f(t) = 1, g(t) = e^(-t) - e^(-2t), then y = (f * g) = ∫[ e^-(t-τ) - e^-2(t-τ) ]dτ, from 1 to t = (1/2) - e^-(t-1) - (1/2)e^-2(t-1), which is the correct answer according to my textbook.
But, y = (g * f) = ∫[ e^(-τ) - e^(-2τ) ]dτ, from 1 to t = -e^(-t) + (1/2)e^(-2t) + e^(-1) - (1/2)e^(-2) =/= (f * g)
I integrated from 1 instead of 0 since r=0 for t < 1.